Prevalence of Hepatitis B, C and HIV Viruses in Blood Donors at Patel Hospital - Rana, Adnan Ali; Ali, Zahid; Amin, Fahad; Sharif, Nimra (LIAQUAT MEDICAL RESEARCH JOURNAL, 2020)
Globally around 70 million people are suffering from chronic hepatitis B virus (HBV), chronic hepatitis C virus (HCV) and Human Immuno Deficiency Virus (HIV) infections. Owing to inadequate health care facilities and lack of awareness at large, Pakistan is also adversely affected by these diseases. The objective of this study was to determine the frequency of transfusion transmitted viral infections among voluntary blood donors at Patel Hospital Karachi. All blood donors who visited the blood bank at Patel Hospital Karachi were processed. Participants were selected through stringent selection criteria ensuring safety of both the donor and recipient. Specimens from donated blood were screened for hepatitis B surface antigen (HBsAg), antibody against hepatitis C virus (anti HCV) and antibody against Human Immuno Deficiency Virus type 1 (HIV-1) and type 2 (HIV-2) using chemiluminosence based assays. A total of 4034 donors were processed in this study. Based on the selection criteria, 424 donors were deferred and 3610 were enrolled into the study. Anemia was the most common cause for deferral. Among the study participants 69 (1.91%) donors were HBsAg, 81(2.24%) were Anti HCV and 2 were Anti HIV-1/HIV-2 infected. It was concluded that the most common cause for donor deferral is anemia and that a significant number of voluntary blood donors are infected with (HBV), (HCV) and (HIV). Blood products should, therefore, be properly screened for these infections.